Antiparasitarios de uso veterinario combinados por medio de nanotecnología - Sanguinetti, Ana Paula; Astorga, Laura; Lillo, Cristian R.; Calienni, María Natalia; Montanari, Jorge (EdiUNS; Universidad Nacional del Sur, 2024)
.
Keywords: Ciencias agrícolas::Biotecnología agrícola